2017
DOI: 10.1002/oby.21862
|View full text |Cite
|
Sign up to set email alerts
|

A Community‐Based Intervention Program's Effects on Dietary Intake Behaviors

Abstract: The intervention group improved dietary intakes of fat and fast foods but not fruits, vegetables, or beverages over the short term. Our intervention had no long-term effect on dietary intake behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Lesson four included effective ways to help with parenting (e.g., listen and talk to children, be consistent, get down to the child’s eye level to communicate with the child, and use a responsibility chart). A detailed description of lessons five to ten (healthy eating and physical activity) has been published elsewhere [21, 23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesson four included effective ways to help with parenting (e.g., listen and talk to children, be consistent, get down to the child’s eye level to communicate with the child, and use a responsibility chart). A detailed description of lessons five to ten (healthy eating and physical activity) has been published elsewhere [21, 23].…”
Section: Methodsmentioning
confidence: 99%
“…To summarize, we did not find significant differences in body weight between the intervention and comparison groups at the end of the intervention (T2) and at three-month follow-up (T3) [20]. The secondary outcomes of MIM included dietary intake, which has been previously published [21]; physical activity (to be published elsewhere); and psychosocial health: stress, depressive symptoms, and positive and negative affect. The analyses for the secondary outcomes focused on examining the differences in these variables between the intervention and comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…Without links between stress and fat or fast food intake in the model, the intervention did not reduce fat intake (top section of Table 1), which contradicts a published result using different analyses [21]. The non-significant finding is attributed to a negative indirect effect (intervention → stress → fat intake; Table 1 bottom section) added to a positive direct effect (intervention → fat intake; Table 1 middle section) resulting in a small and non-significant positive total effect (intervention → fat intake; Table 1 top section).…”
Section: Total Effects Of Intervention and Covariatesmentioning
confidence: 57%
“…Chang and colleagues conducted a randomized controlled community-based lifestyle behavior intervention (16-week) for low-income overweight or obese mothers of young children [19]. They found that the intervention significantly reduced stress [p < 0.01, Cohen D (d) = 0.34] [20], and fat (p < 0.05, d = 0.24) and fast food intakes (p < 0.05, d = 0.33) [21] at the end of the 16-week lifestyle intervention after adjusting baseline assessment. In the current secondary analysis, we conducted new analyses using cross-sectional data from 338 low-income overweight or obese mothers of young children (intervention group = 212, comparison group = 126) who completed the phone interview at the end of the 16 week-intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It could reach more people and offer support that is more continuous while it was hard to continue face-to-face peer support for some people, busy middle-aged worker especially ( 13 ). Notably, the positive effect of peer support on individuals’ dietary intake behaviors did not appear to last at follow-up assessment, partly because they had relapsed to previous habits without awareness after intervention ( 29 ). Peer support intervention might be a feasible alternative for individuals with over-weight and obesity in places with limited professional resources, and innovative approaches with continuous peer support are needed.…”
Section: Discussionmentioning
confidence: 99%